PYROLYTIC OIL - A PRODUCT OF FAST PYROLYSIS OF WOOD RESIDUES FOR ENERGY RESOURCES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The application of renewable energy resources for energy production becomes increasingly urgent worldwide. Fast pyrolysis is one of the trends of obtaining liquid fuel from solid biomass.The aim of the present study was to investigate the yield, chemical composition, physical properties and water amount of hardwood pyrolytic oil (PO) depending on the pyrolysis and pre-treatment conditions in an ablative type reactor.The results of the analysis of the heat capacity of pyrolytic oil show an increase in this parameter from 12 MJ/kg (without drying) to 15-16 MJ/kg, drying the wood, and then pyrolysing it.Pyrolytic oil with a decreased amount of pyrolytic water and a high heat capacity was obtained in an ablative type reactor, drying the wood and then pyrolysing it. For the pyrolytic oil obtained in the two-stage fast pyrolysis equipment process, pH increases.